Service Tasmania ([Tasmania] : Service Tasmania, 2001)
Portal for online Government services and information, including state, commonwealth, and local government
Mode of access: Internet via World Wide Web. Available at: http://odi.statelibrary.tas.gov.au
Keywords: Government information - Databases - Tasmania; Service Tasmania Online; service tasmania; service tasmania; service tasmania; service tasmania online; service tasmania online;.